Deficiency of Interleukin-1 Receptor Antagonist: A Case with Late Onset Severe Inflammatory Arthritis, Nail Psoriasis with Onychomycosis and Well Responsive to Adalimumab Therapy - Necil Kutukculer; Anne Puel; Sanem Eren Akarcan; Kunihiko Moriya; Neslihan Edeer Karaca; Melanie Migaud; Jean-Laurent Casanova; Guzide Aksu (Case Reports in Immunology)
DIRA (deficiency of the IL-1Ra) is a rare condition that usually presents in the neonatal period. Patients with DIRA present with systemic inflammation, respiratory distress, joint swelling, pustular rash, multifocal osteomyelitis, and periostitis. Previously, we reported a patient with a novel mutation in IL1RN with a healthy neonatal period, a late-onset of pustular dermatosis, inflammatory arthritis, and excellent response to canakinumab treatment. Herein, we are presenting a new case of late-onset DIRA syndrome, carrying a different mutation and showing different clinical findings. This patient is the first one in the literature with the inflammatory arthritis, nail psoriasis, and onychomycosis and with her remarkable response to monoclonal antibodies. The case responded well and fully recovered after treatment with adalimumab, but not with canakinumab. The DIRA disease can lead to death from multiple organ failures and if recognized early, the treatment with replacement of the deficient protein with biologic agents induces rapid and complete remission. Therefore, clinical symptoms should be learned exactly by the pediatricians, pediatric rheumatologists, and immunologists; and molecular analysis targeting this defect must be performed as early as possible.